An internet of things for water utility monitoring and control - Madala, Kranthi; Divya Bharathi, D; Chowdary Polavarapu, Sushma (International Journal of Engineering and Technology, 2018)
The aim of thepaper is to advise more efficient water monitoring and control approach to reduce the water loss. This may assist users, operatorsto improve water control systems, by using the emerging technology. Net of factors is one of the essential strategies for making consumption of water assets more efficient and for developing extra utilityproperstructures. Now–a–days the water monitoring and control is dealing with a few issues. As an example the manipulate structures usedby using waterdistributionutilities ought to function over a hugevicinity. Massive water utilities go through transit losses due to leaks and burstpipes. An IoT answer for water tracking and control ambitions at being capable of gather more than one device, analyzing these recordsand dispatching themand consequences from processing to diverse programs or to other devices.